SMART CITY DEVELOPMENT PLANNING: A STUDY OF STRUCTURED LIBRARY (SYSTEMATIC LITERATURE REVIEW) - Devi Novita Sari; Salahudin Salahudin (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Smart city planning is a smart city concept that can help people in an area to be able to manage existing resources more efficiently. This concept also utilizes advances in information technology to run the wheel of life more efficiently, so that it can help improve the quality of better urban planning. The purpose of this research is to find out about the planning of sustainable smart city development by looking at the application in various regions. This research was conducted using the literature review method, which is done by rereading and reviewing the main ideas on the same topic. The focus of this research is to use literature studies of previous researchers with the same topic. Sources of data used are documents related to research obtained from the SCOPUS database and processed using the VOSViewer application. Data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions. The results obtained from the study show that development planning through smart cities has been widely applied in almost all regions of the world. However, there are several obstacles in the implementation process, such as there are still many people who do not understand the use of technology. However, seeing the many benefits that can be obtained from development planning through smart cities, its implementation should continue to be optimized.